Estrategia de banca móvil y nivel de aceptación de clientes microempresarios de Caja Arequipa, agencia San Hilarión - Lima 2020 - Ríos Sánchez, Yolving Cleiver (2022)
The research carried out was aimed at determining how the Mobile Banking Strategy is accepted by the microentrepreneur clients of Caja Arequipa, Agencia San Hilarión - Lima, having the District of San Juan de Lurigancho Province of Lima as a geographical setting, and as an entity analyzed the Municipal Savings and Credit Fund of Arequipa - San Hilarión Agency, the research carried out according to its scope is descriptive, not experimental, the Inductive-Deductive Method, Hypothetical-Deductive Method, data collection was used and the survey as a research technique, to validate the reliability of the data collection instruments, Cronbach's Alpha method was applied, obtaining an alpha of 0.828 for both data collection instruments, for the Mobile Banking variable an alpha was determined equal to 0.800, and for the variable Acceptance of clients with an alpha equal to 0.808, which shows the reliability of said inst ruments; the population was made up of 1,961 microentrepreneur clients, we worked with a sample of 139 microentrepreneur clients, the data collection instrument was applied to said sample, with the information obtained and processed it was possible to meet the objectives of the investigation, contrast the hypothesis, and determine as the main result that the Mobile Banking variable has a significant positive influence on the Acceptance Level variable, likewise, the results were processed by the statistical program SPSS Version 25.